Effect of Open-Ended PHC Pile Installation during Embankment Widening on the Surrounding Soil - Li, Guo-Wei (2020)
This paper investigates the effect of jacking two groups of open-ended prestressed high-strength concrete (PHC) piles on an existing highway embankment based on field measurements of excess pore pressure and lateral soil displacement. Excess pore pressure due to pile jacking increased with depth and decreased with increasing distance from the pile; the influence reached a distance of 43 pile diameters from the pile axis. For pile groups, the amount of excess pore pressure dissipated decreased with increasing depth and varied from 54% to 100% in 20 days. Lateral soil displacement and excess pore pressure continued to increase for a period of time after the end of pile jacking, and this could have resulted in significant inclination of piles if pile installation was too quick and pile spacing was too small. Lateral soil displacement due to pile group decreased with decreasing distance to the existing embankment as a result of higher soil stiffness and strength produced by the embankment loading. The effect of pile group installation on the existing embankment was negligible.